(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the diagnostic accuracy of the 50gm glucose challenge test for detecting gestational diabetes by taking a 75gm oral glucose tolerance test as the gold standard among high-risk pregnant women. METHODOLOGY: A descriptive cross-sectional design study was undertaken at Sobhraj Maternity Hospital, Karachi, on a group of 195 high-risk pregnant women, aged 20 – 35 years with gestational age during 20 to 32 weeks. The diagnostic accuracy of the 50-gram glucose challenge test (GCT) was evaluated against 75-gram oral glucose tolerance test (OGTT). Participants first underwent 50-gram GCT, followed by a venous blood sample collection. Within one week, with at least a three-day gap, the 75-gram OGTT was performed similarly. A blood glucose level above 140 mg/dl on the OGTT confirmed gestational diabetes mellitus (GDM). The data was analyzed by SPSS version 26. RESULTS: The average age of participants was noted as 27.69 ± 4.11 years, the diagnostic accuracy of the 50gm glucose challenge test for detecting the gestational diabetes was 91.28%, with a sensitivity of 86.84%, sensitivity of 92.36%, positive predictive value of 73.33%, and negative predictive value of 91.28%. CONCLUSION: The current study findings show the significant diagnostic accuracy with 50 g GCT for GDM with fair sensitivity, but high specificity. The high negative predictive value supports the usage of this tool as a cost effective screen, although its moderate positive predictive value mandates confirmatory testing with the 75-gram oral glucose tolerance test (OGTT). Future research should refine screening protocols to improve early detection and management of GDM, ultimately enhancing maternal and fetal outcomes.